2016
DOI: 10.1111/acem.12957
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Hematoma Characteristics Associated With Intracranial Injury in Pediatric Minor Head Injury

Abstract: Objectives: Minor head trauma accounts for a significant proportion of pediatric emergency department (ED) visits. In children younger than 24 months, scalp hematomas are thought to be associated with the presence of intracranial injury (ICI). We investigated which scalp hematoma characteristics were associated with increased odds of ICI in children less than 17 years who presented to the ED following minor head injury and whether an underlying linear skull fracture may explain this relationship.Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
(80 reference statements)
6
26
0
1
Order By: Relevance
“…In addition, the CHALICE definition includes a large SH size (>5 cm) and a younger age (<1 year), which have been shown to be independently associated with intracranial injury. The PECARN subanalysis, consistent with other studies, found that younger patient age, increased SH size, non-frontal SH location and severe injury mechanism were independently associated with TBI on CT 6 21–23. In children meeting the CHALICE definition of isolated SH, the frequency of ciTBI/csII clearly supports the performance of CT scan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the CHALICE definition includes a large SH size (>5 cm) and a younger age (<1 year), which have been shown to be independently associated with intracranial injury. The PECARN subanalysis, consistent with other studies, found that younger patient age, increased SH size, non-frontal SH location and severe injury mechanism were independently associated with TBI on CT 6 21–23. In children meeting the CHALICE definition of isolated SH, the frequency of ciTBI/csII clearly supports the performance of CT scan.…”
Section: Discussionsupporting
confidence: 84%
“…While previous guidelines recommended skull X-rays in children with isolated SH, based on evidence showing the association between skull fracture and TBI, other studies have shown that up to 50% of TBI can occur in the absence of a skull fracture 9 22 25–28. Point-of-care ultrasound is increasingly replacing skull X-rays for the identification of skull fractures in children with traumatic SHs, showing good accuracy for fractures identification compared with CT scan 29 30.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp haematomas were frequently characterised as ‘boggy’. This term has been used in some studies as an indicator of larger size and increased risk of skull fracture . However, there is no consensus of what constitutes a ‘boggy’ swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp haematoma may be the only sign of an acute brain lesion in infants but is most frequently associated with isolated linear skull fractures, the majority of which do not require neurosurgical intervention . More recent research has suggested that patients with an isolated scalp haematoma have a negligible risk of requiring neurosurgical intervention …”
mentioning
confidence: 99%
“…Vários estudos afirmam que hematomas volumosos e noção de afundamento ósseo são fatores de risco para fratura e/ou LIC. 3,13,19,35 Na verdade, estes sinais são considerados de alarme pelos três algoritmos de decisão clínica mais utilizados internacionalmente na abordagem dos TCE ligeiros em idade pediátrica (PECARN, CHA-LICE e CATCH). 11,19,25 Não podemos deixar de comentar que duas crianças com perda de conhecimento superior a cinco minutos e uma criança com sinais focais à admissão não realizaram TC-CE, não se respeitando o protocolo em vigor na nossa instituição.…”
Section: Discussionunclassified